Developing the Digital and Non-Digital (Arabic - Indonesian) Bilingual Dictionary to Improve the Vocabulary Proficiency of Islamic Elementary School Students/ تطوير المعجم ثنائي اللغة (عربية – إندونيسية) الرقمي وغير الرقمي لتلاميذ المدرسة الابتدائية - Makiatul Madaniah; Nurul Murtadho; Nurhidayati Nurhidayati (Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2020)
يهدف هذا البحث إلى انتاج المعجم ثنائي اللغة الرقمي وغير الرقمي لتلاميذ المدرسة الابتدائية ومعرفة مدى صلاحيته ومدى فعاليته في تعليم اللغة العربية. و المفردات مصحوبة بالأمثلة في الجملة البسيطة والصورة الجذابة. المنهج المستخدم في هذا البحث هو منهج البحث والتطوير عند بورغ وغال. وطريقة جمع البيانات هي طريقة الملاحظة والمقابلة والاستبانة وورقة التحقيق والاختبارين أي الاختبار القبلي والاختبار البعدي. ونتيجة هذا البحث هي (1) قد تم تطوير المعجم ثنائي اللغة (عربية – إندونيسية) الرقمي وغير الرقمي لتلاميذ المدرسة الابتدائية، (2) اعتمادا على النتيجة المحصولة من خبير المواد وخبير الوسائل التعليمية واستبانة استجابة الدارسين، هذا المعجم ذو صلاحية جيدة جدا، (3) بناء على نتيجة التجربة الميدانية التي تمت تنفيذها بالاختبار القبلي والاختبار البعدي من قبل التلاميذ، فقررت أن هذا المعجم فعال جدا للاستخدام في تدريس اللغة العربية ويمكن ترقية نتيجة التلاميذ في تدريس اللغة العربية. This study aims to produce a product in the form of an Arabic-Indonesian dictionary digital and non-digital to improve the vocabulary skills of students at Islamic elementary school and to know the level of validity and the level of effectiveness. Equipped with simple sentence examples and an attractive picture. The research model used is the Research and Development model based on model of Borg & Gall. Methods of data collection in the form of observation, interview, questionnaire, validation sheets, and two tests, namely pre-test and post-test. The result of this research is (1) a bilingual (Arabic-Indonesian) digital and non-digital dictionary has been developed for the students of Islamic elementary school, (2) depending of the result obtained from the material expert and media expert and the students’ response questionnaire, this dictionary is of very good validity, (3) based on the result of the field experiment that was carried out through the pre-test and post-test by students, it is considered that this dictionary is very effective for improving vocabulary efficiency and for increasing the value of student in the Arabic learning